Beyond vision loss: the impact of glaucoma on the brain - Trinita Jude Hamilton; Bettina E. Kalisch (Frontiers in Cell and Developmental Biology, 2025)
Glaucoma, a leading cause of irreversible blindness, is characterized by optic disc cupping and retinal ganglion cell (RGC) degeneration. Recent research highlights the broader impacts of glaucoma on the brain. Transsynaptic neural degeneration extends the RGC damage through the visual pathway and various other regions in the brain, leading to structural and functional changes. These neurodegenerative effects may result in cognitive impairment, affecting patients’ daily activities and quality of life. Understanding the connection between glaucoma, the brain, and cognition is essential for intervention and developing comprehensive treatment strategies that address visual and neurological impairments, ultimately improving patient outcomes. This review examines the existing literature on the links between glaucoma pathology and the brain and explores the impacts on cognition and quality of life.